Charles Perrone and Cristopher Dunn, eds .. Brazilian Popular Music and Globalization. Gainesville: University Press of Florida, 2001. xii, 288 pp. - Araujo, Samuel (Current Musicology, 2002)
This book addresses the dynamics oflocally emerging musical expressions in their complex creative reactions to the global politics of cultural diffu-sion. Its contents are mainly derived from selected iinterdisciplinary con-ference papers, along with a few scholarly articles produced by members of the Brazilian academic project Socio-Anthropology of Music in Bahia (S.A.M.B.A.). The theme for these academic variations is set up by a pro-vocative essay previously published in the New York Times by the prominent Brazilian singer, composer, and writer Caetano Veloso.